Agri-Food 4.0 : Innovations, Challenges and Strategies - Mor, Rahul S.; Kumar, Dinesh (Professor of supply chain management); Singh, Anupama (Advanced series in management, 2022)
Agri-Food 4.0: Innovations, Challenges and Strategies addresses new research on digital technologies in the Agri-Food industry, including smart packaging, smart warehousing, effective inventory control, blockchain technology, artificial intelligence, and other Industry 4.0 concepts.